KKN-T Program: Environmental Education Through the Creation of Road Signs and Handicrafts from Recycled Materials for the Community of Pintu Batu - Hafiz Pandu Tizaldi; Made Suardha Puspa; Nurul Aini; Putri Fajar Wati; Mupiansa Mupiansa; Dimas Aulia Trianggana; Merry Rullyanti; Hendri Alamsyah (Universitas Dehasen Bengkulu, 2026)
Pintu Batu Village faces challenges regarding the completeness of environmental information infrastructure in the form of street signs and the management of inorganic waste, which has not been utilized creatively. This community service activity aims to improve environmental order and resident creativity through mutual cooperation, the installation of street signs in RT 02, and handicraft training using recycled materials. Furthermore, early childhood education regarding the importance of proper waste disposal was provided to the children of TK Cerdik Pintu Batu through engaging approaches such as morning exercises and collective coloring activities. The method employed is a participatory-educational approach involving coordination with local officials and direct handson practice with the residents. The results of the activity indicate an increase in citizen participation in mutual cooperation and the creation of recycled products such as flower pots from plastic bottle and beverage baskets from plastic cup waste. The existence of new street signs facilitates easier navigation within the neighborhood, while the educational activities at the kindergarten level strengthen the foundation of environmental awareness from an early age.